Enflasyon hedeflemesi dünya’ da ve Türkiye’ deki uygulamaları - Uysal, Murat (My University, 2001)
Ülke ekonomilerinin öncelikle çözümlemeleri gereken sorunların başında enflasyonu düşük düzeylere çekerek uzun dönemde fiyat istikrarını sağlanması gelmektedir. Bunu gerçekleştirmek amacıyla, merkez bankalarına tam bağımsızlık verilmesi yönündeki politika uygulamasına ek olarak, son zamanlarda giderek önem kazanmış olan, EH adı altında yeni bir yaklaşım geliştirilmiş bulunmaktadır. Bağımsız bir kimliğe sahip para otoritesi ile siyasi otorite arasında sözleşme esasına dayalı bu yaklaşım, para otoritesini geniş yetkilerle donatmakta ve sorumluluklar yükleyerek para politikasını fiyat istikrarının sağlanması yönünde yürütmekle yükümlü kılmaktadır. 1970 ve 1980'li yıllarda birçok ülke para politikası çerçevesinde para talebinin istikrarlı olduğu varsayımıyla parasal büyüklükleri ara hedef olarak seçmişlerdir. Bu hedef değişkenler ile gelir, fiyat ve paranın dolaşım hızı arasında istikrarlı bir ilişkinin varolduğu görüşünden kaynaklanmıştır. Ancak, yapısal değişim ve finansal liberalizasyon programları uygulayan birçok ülkede paranın dolanım hızındaki istikrarın kaybolması, yeni finansal araçların ortaya çıkması ve finans sektöründeki hızlı büyüme sonucu para talebindeki istikrar bozulmuş ve gelişmeler parasal büyüklüklerin ara hedef olarak seçilmesini güçleştirmiştir. Ara hedef olarak seçilen parasal büyüklüğün, enflasyon ve cari gelir için nominal çıpa olma özelliğini yitirmesi, ekonomistleri alternatif politika arayışlarına yöneltmiştir. Son yıllarda, ara hedefler kullanılmasını gerektirmediğinden enflasyonun doğrudan hedeflenmesi politikası alternatif bir para politikası olarak ortaya çıkmıştır. EH yaklaşımı gelecek döneme ya da dönemlere ilişkin enflasyon tahminlerinin belirlenerek kamuoyuna açıklanmasını gerektirmekte, katı biçimde uygulandığı ülke örneklerinde görüldüğü gibi, bu hedeflerin gerçekleştirilmesinden para otoritesini sorumlu tutmaktadır. EH yaklaşımı, 1990 yılında Yeni Zelanda'yla başlamış olup, bugüne dek daha çok gelişmiş ekonomilerde başta olmak üzere geniş bir uygulama alanı bulmaktadır. Şimdiye kadar uygulama sonuçları dikkate alındığında, yaklaşımın yapabilecekleri ve yapamayacakları konusunda farklı görüşler bulunmakla birlikte, çok yüksek oranlarda enflasyon yaşayan ülkeler dışında, uygulanabilir özellikler taşıdığı ve başarılı olduğu değerlendirmesi yapılabilir. Diğer yandan rejimin gelişmekte olan ülkelerdeki uygulanabilirliği de ayrı bir tartışma konusudur. Bu çalışmada EH rejiminin kavramsal çerçevesi, ön koşulları, uygulanmasına yönelik stratejik ve teknik özellikleri, genel kabul gören avantaj ve dezavantajları ile bu rejimi uygulayan gelişmiş ve gelişmekte olan ülke deneyimleri hakkında bilgi verilmek suretiyle konunun ana hatları çizilmeye çalışılmıştır. Son bölümde ise EH politikasının Türkiye'de uygulanabilirliği sorusuna cevap aranmıştır.

INFLATION TARGETING: WORLD AND TURKISH EXPERIENCES The unhappy experience of Latin American and East Asian countries with pegged exchange rate regimes who subsequently found themselves in deep financial crises in the 1990s has led emerging market economies to search for alternative nominal anchors. Targeting inflation, a monetary policy strategy which has been successfully used by a number of industrialized countries, has thus become an increasingly attractive alternative that has been adopted by a growing number of emerging market countries, including Chile, Brazil, and Poland . In this paper, I outline what inflation targeting involves for these countries and discuss the advantages and disadvantages of this monetary policy strategy. The bottom line is that although inflation targeting is not a remedy for all troubles and may not be appropriate for many emerging market countries, it can be a highly useful monetary policy in a number of them. Conceptual Framework of Inflation Targeting Inflation targeting is a monetary policy strategy that encompasses five main elements: 1) the public announcement of medium-term numerical targets for inflation; 2) an institutional commitment to price stability as the primary goal of monetary policy, to which other goals are subordinated; 3) an information inclusive strategy in which many variables, and not just monetary aggregates or the exchange rate, are used for deciding the setting of policy instruments; 4) increased transparency of the monetary policy strategy through communication with the public and the markets about the plans, objectives, and decisions of the monetary authorities; and 5) increased accountability of the central bank for attaining its inflation objectives. The list should clarify one crucial point about inflation targeting: it entails much more than a public announcement of numerical targets for inflation for the year ahead. This is important in the context of emerging markets' countries because many of them routinely reported numerical inflation targets or objectives as part of the government's economic plan for the coming year, and yet their monetary policy strategy should not be characterized as inflation targeting, which requires the other four elements for it to be sustainable over the medium term. The Advantages of Inflation Targeting: The Inflation targeting regime has several advantages as a monetary policy strategy when compared with the other policy regimes. 1) Inflation targeting provides a nominal anchor for monetary policy and inflation expectations. 2) In contrast to the exchange rate targeting, Inflation targeting gives opportunity to respond shocks hitting to the economy and to focus domestic considerations 3) Inflation targeting does not require a stable relationship between monetary aggregates and inflation as in monetary targeting. It uses all available information in the formation of the policy setting. 4) As it is explained above, monetary policy shows its impact on the economic activity with long and variable lags. inflation targeting regime gives an explicit role to the lags of monetary policy in the choice of policy instruments. 5) It is possible in the inflation targeting regime to decrease the possibility of falling into time inconsistency trap by decreasing the pressure coming from the politicians in order to stimulate the economic activity. 6) The other advantage of the inflation targeting regime is its great emphasis on the regular communication with the public and transparency. This property have important role in the success of the Inflation targeting in the industrialized countries. The policymakers in the developed countries use every opportunity to communicate with the public like public speeches and a step further by means of inflation reports. 7) Transparency of the policy has inclination to make the policy more accountable to the public and continuous success of the policy in reaching the numerical targets increases the public support for the central bank. 8) One of the advantages of inflation targeting regime is its clarity for public understanding compared with the nominal income targeting. In the nominal income-targeting regime, there is no decomposition for the income component and price component. So, it might be difficult for the public to built price expectations. In addition, the inflation-targeting regime serves as an anchor for wage and the price setters and the existence of such an anchor increases the credibility of the policy. After a shock hits the economy, the necessary action of the central bank must be taken to offset the impact of the shock decreases. The Disadvantages of Inflation Targeting: 1) The inflation-targeting regime has been criticized due to its overemphasis on inflation, its rigid structure, its negative impacts on the economic growth and its exclusion other goals like output stabilization.However, the countries' announcement of the targets above the zero inflation rates reflects the fact that the central banks does not ignore the output growths totally and it takes into account a possible deflation and the undesirable impacts of deflation on the economic activity. 2) It is claimed that there is only weak central bank accountability in inflation targeting because in contrast to exchange rate and monetary aggregates inflation is difficult to control and the policy instruments show their impact on inflation with long and variable lags. This problem is especially severe in the developing countries when the rates of inflation are being brought down from high levels. In this situation, there will be large forecast errors and frequent target misses. Therefore, it will be difficult for the central bank to explain the reason for the deviations from the target and to gain credibility, which is central to the inflation targeting regime. Inflation targeting will be more effective if it is started to implement this regime after successful disinflation. It is what Chile did. Another factor that has influence on the ability of the central banks to control inflation is the large existence of the government-controlled prices and this factor is of significant importance for the developing countries. Successful inflation targeting implementation requires high coordination between the people who determine these prices and the monetary policymakers or the exclusion of these prices from the targeted rate in this circumstance. Moreover, inflation forecasting procedure in these countries should take into account the timing and magnitude of the changes in those prices. 3) Inflation targeting may not prevent fiscal dominance. In the long run, large fiscal deficits will cause either monetization of the deficits or devaluation and they will result in high inflation. 4) Exchange rate flexibility required by inflation targeting might cause financial instability. 5) There are some economists who argue that the inflation targeting regime is too discretionary and it may cause policy makers to follow overly expansionary policies. However, as it is explained in this paper, inflation targeting regime increases the accountability and transparency of the policy. Accountability increases the costs of policy mistakes for policy makers and transparency makes difficult to conduct overly expansionary policy without it being noticed. So, it does not seem plausible to assert that the monetary policy in the inflation targeting regime is too discretionary. 6) Some economists argue that inflation targeting is too rigid and it impedes the monetary authorities from responding to the shocks hitting the economy. However, it can be argued that inflation targeting is far from being a rigid rule; it can be evaluated as 'constraint discretion'. It does not impose simple rules about the conduct of the monetary policy. Contrary to simple rules, inflation targeting regime obligates policy makers to use all available information in order to achieve the target.
Keywords: Bankalar Ve Bankacılık; Ekonomi; Enflasyon; Finansman ekonomisi; Para; Paranın değeri